158k views
1 vote
6b.) Hence, or otherwise, evaluate g(f(3))

6b.) Hence, or otherwise, evaluate g(f(3))-example-1

2 Answers

4 votes

Answer:

-25

Explanation:

g(f(3))= g(-5)

=4(-5)-5

= -20-5

=-25

User Pojo
by
5.4k points
6 votes

Answer:


g(f(3))=-25

Explanation:

We have the two functions:
f(x)=-2x+1 and
g(x)=4x-5.

And we want to evaluate
g(f(3)).

So, let's evaluate f(3) first. Substitute 3 into f(x). This yields:


f(3)=-2(3)+1

Multiply and add:


f(3)=-6+1=-5

So, our expression is now:


g(f(3))\Rightarrow g(-5)

Substitute -5 for g(x):


g(-5)=4(-5)-5

Multiply and subtract:


g(-5)=-20-5=-25

Therefore:


g(f(3))=-25

User Tom Headifen
by
5.6k points